Effects of nano-selenium on cecum microbial community and metabolomics in chickens challenged with Ochratoxin A - Fang, Manxin; Hu, Wei; Liu, Ben (Frontiers in Veterinary Science, 2023)
Ochratoxin A (OTA) is a widely distributed mycotoxin. Nano-selenium (Nano-Se) is an emerging form of selenium known for its superior bioavailability, remarkable catalytic efficiency, and robust adsorbing capacity. Despite these characteristics, its impact on the microbial community and metabolomics in the cecum of chickens exposed to OTA has been infrequently investigated. This research examined the microbiota and metabolomic alterations linked to OTA in chickens, with or without Nano-Se present. A cohort of 80 healthy chickens at the age of one day was randomly distributed into four groups of equal numbers, namely the Se cohort (1 mg/kg Nano-Se), the OTA cohort (50μg / kg OTA), the OTA-Se cohort (50μg / kg OTA + 1 mg/kg Nano-Se), and the control group. Each chicken group's caecal microbiome and metabolome were characterized using 16S rRNA sequencing and Liquid chromatography coupled with mass spectrometry (LC-MS) analyses. The data suggest that Nano-Se supplementation in OTA-exposed chickens mitigated gut microbiota imbalances by promoting beneficial microbiota and suppressing detrimental bacteria. Moreover, untargeted metabolomics revealed a significant difference in caecal metabolites by Nano-Se pretreatment. Collectively, the dataset outcomes highlighted that Nano-Se augmentation regulates intestinal microbiota and associated metabolite profiles, thus influencing critical metabolic pathways, and points to a possible food-additive product.